2012
DOI: 10.1177/0960327112455670
|View full text |Cite
|
Sign up to set email alerts
|

The role of adenosine receptors on amitriptyline-induced electrophysiological changes on rat atrium

Abstract: We investigated the role of adenosine receptors in amitriptyline-induced cardiac action potential (AP) changes in isolated rat atria. In the first group, APs were recorded after cumulative addition of amitriptyline (1 μM, 10 μM and 50 μM). In other groups, each atrium was incubated with selective adenosine A(1) antagonist (8-cyclopentyl-1,3-dipropylxanthine (DPCPX), 10(-4) M) or selective adenosine A(2a) receptor antagonist (8-(3-chlorostyryl) caffeine, 10(-5) M) before amitriptyline administration. Resting me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs. Cardiovascular toxicity was reversed, when AdR antagonists were employed …”
Section: Organ‐specific Toxicity Of Adenosine Derivatives and Adenosimentioning
confidence: 99%
See 1 more Smart Citation
“…It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs. Cardiovascular toxicity was reversed, when AdR antagonists were employed …”
Section: Organ‐specific Toxicity Of Adenosine Derivatives and Adenosimentioning
confidence: 99%
“…Mellor et al [21] Potential cardiotoxic effects are mediated through inhibition of AdRs (a mechanism of kinase inhibition) Teerlink et al [23] A 1 AdR antagonist, rolofylline, used in patients with acute heart failure showed an increased incidence of seizures and unanticipated increased incidence of strokes D'Ambrosio [26] Comprehensive evaluation of important safety data related to caffeine toxicity Lim et al (2011) [90] An example of dual acting A 2A AdR and A 1 AdR antagonist that undergoes metabolic activation to genotoxic reactive intermediates Rebola et al [124] A 1 AdRs and A 2A AdRs control neurodegeneration processes, whereas A 2A AdR activation decreases neurotoxicity in cultured cortical neurons Ohta and Sitkovsky [5] Discovery of a critical role of A 2A AdR in downregulation of immune response in inflamed normal tissues Thiel et al [80] Demonstration of a critical role of A 2A AdR in case of acute inflammatory lung injury Ohta et al [81] Discovery of a critical and non-redundant role of A 2A AdR in downregulation of immune response in cancerous tissues Hatfield and Sitkovsky [82] Overall summary of important discoveries from Sitkovsky team and related research groups with description of tumour-protecting role of A 2A AdR and importance of A 2A AdR inhibition in cancer immunotherapy agonists. One study from Sabbah et al [36] actually showed promising results for capadenoson (CAP), a partial nonnucleoside A 1 AdR agonist, on left ventricular function in dogs with heart failure.…”
Section: Adenosine Receptor Agonistsmentioning
confidence: 99%
“…[678910] There is only one experimental study about the role of adenosine in cardiovascular effects of the citalopram. [11] It was observed that the negative inotropic and chronotropic effects induced by citalopram can be explained by the inhibition of re-uptake of adenosine or the activation of adenosine A 1 receptors.…”
Section: Introductionmentioning
confidence: 99%